THE ROLE OF THE TRAINING AND PERSONNEL DEVELOPMENT SYSTEM IN PROFESSIONAL GROWTH AND EMPLOYEE SATISFACTION (Development Service Industry Management, 2024)
In the context of modern organizations, the success of enterprises is significantly influenced by the competence and professional skills of their personnel. The employee training and development system plays a crucial role in human resource management, as it enhances qualifications, provides opportunities for career growth, and promotes job satisfaction. A well-planned and effectively organized training system not only helps to achieve the organization's strategic goals but also improves its competitiveness, enables employees to reach their potential, and provides flexibility to adapt to market challenges and changes in the external environment. The purpose of this article is to highlight the importance of the employee training and development system for the success of contemporary organizations, analyze existing research, and identify key areas for further investigation in this field. In particular, the article aims to systematize knowledge about existing approaches to organizing employee training and development, identify unresolved issues, and offer practical recommendations to enhance the effectiveness of these systems in organizations of various types. The article emphasizes that continuous improvement through employee training and development is an essential factor for organizational success in today’s competitive environment. The need to adapt to rapidly changing external conditions exacerbates the demand for higher levels of education, continuous learning, skills enhancement, and the development of new competencies. While training and development are often used interchangeably, these concepts differ in their scope, complementing each other to create a comprehensive approach to increasing professional potential and effectiveness. Training is a short-term activity focused on acquiring specific, specialized knowledge and skills for immediate job performance, whereas development is a long-term process aimed at preparing employees for future roles and career advancement. The system of employee training and development can be characterized as a set of interconnected methods, tools, and processes aimed at improving professional competencies, skills, knowledge, and personal qualities to achieve both individual and organizational goals. This system must ensure a balance between employees' professional growth aspirations and the organization’s need for highly skilled, motivated personnel. Effective training and development programs can also improve employee engagement, reduce turnover, and contribute to overall organizational success. The paper concludes that a well-structured employee development system is essential for organizations aiming for sustainable growth, with an emphasis on personalized approaches to training and the integration of various learning methods.
Keywords: human capital development; learning and development; organizational performance; employee training; talent management